Descriptive Catalogue of the Roman Consular and Family Coins (Denarii) in the Cabinets of the Museum of the Society (Proceedings of the Society of Antiquaries of Scotland, 1873)
[The journal notes that this paper will be published in the Archaeologia Scotica.]